High C-and N-based soil fertility and microbial associations sustain the plant biodiversity of the campo rupestre in Brazil - Baião, Érica E.; Santos, Carlos Henrique B. [UNESP]; Santos, Antônio H.; Marques, Gabrielle; Lima, Júlio Cezar; Rigobelo, Everlon Cid [UNESP]; Scotti, Maria Rita (Elsevier, 2021)
The campo rupestre vegetation in the Serra do Rola Moça State Park (PESRM) grows on ironstone outcrops, forming vegetation islands where plant species establish belowground interactions. This area is circumscribed by several mining companies and, for mined land rehabilitation purpose, we assessed plant species composition, plat-microbial associations, and soil fertility patterns in a preserved campo rupestre. Aside from high plant biodiversity, we found elevated soil fertility in relation to soil CEC (~18 cmol/dm3), organic matter (~115 g/Kg), soil C (~ 53.3 g/Kg), humic (~12.5 g/Kg) and fulvic (~8.9 g/Kg) acids, soil N (~4 g/kg) and a low C:N ratio (~12). The overall nutrient levels were higher than or comparable to those of other preserved sites in Brazil. The prevalent legume Mimosa calodendron, hosting N-fixing and plant growth-promoting bacteria in its nodules, was considered an N source to the soil, as evidenced by the elevated leaf N content and the greater depletion of leaf δ15N compared to other families. However, leaf N was parsimoniously distributed among biogeochemical islands and within different plant species and families, which was attributed to a common mycorrhizal network (CMN) formed by arbuscular (AMF) and orchid mycorrhizal fungi (OMF), suggested by general root mycorrhizal colonisation and soil phospholipid fatty acid (PLFA) analyses. We revealed that a high C- and N-based soil fertility constitutes a natural pattern of fertility, which is maintained by below-ground associations and is sufficient to sustain plant biodiversity. For rehabilitation purposes, this natural soil fertility of preserved sites should be maintained by integrating the biogeochemical relations involving plant communities and microbial associations.
Keywords: Arbuscular mycorrhizal fungi; Biological nitrogen fixation; Humic acids; Orchid mycorrhizal fungi; Phospholipid fatty acids; Rehabilitation